2017
DOI: 10.1080/08916934.2017.1300884
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A1 as a target for managing murine pristane-induced systemic lupus erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a polygenic pathological disorder which involves multiple organs. Self-specific B cells play a main role in the lupus pathogenesis by generating autoantibodies as well as by serving as important autoantigen-presenting cells. Autoreactive T lymphocytes, on the other hand, are responsible for B cell activation and proliferation, and cytokine production. Therefore, both factors promote the idea that a down-modulation of activated self-reactive T and B cells involved in the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…Incubation of PBMCs isolated from SLE patients with anti‐ANX A1 antibody reduced the expression of CD25 + /CD69 + activation markers on activated T cells, suppressed the cell proliferation of dsDNA‐specific IgG antibody‐secreting plasma cells in a dose‐dependent manner, and induced B and T cells apoptosis of activated lymphocytes. Similar results were observed in pristane‐induced murine lupus using the same antibody, suggesting shared mechanisms of T cell activity regulation through the ANX A1–FPR2 signalling pathway . The accumulated data suggest a more complex relation between ANX A1, the monoclonal antibody and apoptosis, respectively, rather than a simple pro‐ or anti‐apoptotic effect .…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Incubation of PBMCs isolated from SLE patients with anti‐ANX A1 antibody reduced the expression of CD25 + /CD69 + activation markers on activated T cells, suppressed the cell proliferation of dsDNA‐specific IgG antibody‐secreting plasma cells in a dose‐dependent manner, and induced B and T cells apoptosis of activated lymphocytes. Similar results were observed in pristane‐induced murine lupus using the same antibody, suggesting shared mechanisms of T cell activity regulation through the ANX A1–FPR2 signalling pathway . The accumulated data suggest a more complex relation between ANX A1, the monoclonal antibody and apoptosis, respectively, rather than a simple pro‐ or anti‐apoptotic effect .…”
Section: Discussionsupporting
confidence: 70%
“…Nevertheless, we found that more than 20% of SLE patients' T cells and only 4% of healthy donors' T cells expressed ANX A1 on the outer membrane leaflet. We studied the effect of anti-ANX A1 in the Murphy Roths large/lymphoproliferation (MRL/lpr) and pristane-induced lupus models, and discovered that ANX A1 is also expressed on the surface of murine B cells, reaching significant levels for the BALB/c mice (up to 20% of splenocytes of animals with induced SLE and approximately 10% of healthy animals) [19]. Contrary to our murine experiments, human B cells exhibited low expression of ANX A1 (1-3%) in SLE patients and less than 1% in healthy donors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include glomerulonephritis, vasculitis, splenomegaly, hypergammaglobulinemia and the production of anti-dsDNA antibodies and autoantibodies to other nuclear components. 20,21 Previously, we employed a pristane-induced mouse model of SLE in Balb/c mice and humanized mouse SLE model in order to suppress disease activity by a monoclonal anti-ANX A1 antibody. The treatment of sick animals with this antibody led to downregulation of IgG anti-dsDNA antibody-secreting plasma cells and of proteinuria, improved kidney histology and prolonged survival compared with the control groups.…”
Section: Introductionmentioning
confidence: 99%
“…As with many other multifunctional mediators, AnxA1 plays a homeostatic role in the immune system as it can exert both positive and negative functions depending on the contexts. In the context of T cells, studies have indeed provided contrasting and opposite results showing that it can act as both a positive [18][19][20][21][22][23][24][25][26][27] and a negative modulator of T cell activation [27][28][29][30] . All these studies have been done using either exogenously administered recombinant AnxA1 (and its mimetic) or AnxA1-deficient mice where the protein is absent in every immune cell.…”
Section: Introductionmentioning
confidence: 99%